Queens and mistresses of Renaissance France - Wellman, Kathleen (Yale University Press, 2013)
Agnès Sorel: the first official royal mistress -- Anne of Brittany: the limits and prospects of a queen -- The women of the court of Francis I: wives and mistresses, sister and mother -- Diane de Poitiers: an idealized mistress -- Catherine de Medici: king in all but name -- Marguerite de Valois: scandalous queen, femme savante -- Gabrielle d'Estrées: nearly a queen